An incremental approach using local-search heuristic for inventory routing problem in industrial gases. (2nd September 2015) - Singh, Tejinder; Arbogast, Jeffrey E.; Neagu, Nicoleta
Highlights: A novel incremental approach using local search to solve an IRP. A novel objective function to reach global optimal solution with a short-term horizon. Large-scale inventory routing problems solved effectively in less than 15 min. 15 real-life test cases showing the effectiveness of the approach. Abstract: In this paper we solve the inventory routing problem (IRP) occurring in industrial gas distribution where liquefied industrial gases are distributed to customers that have cryogenic tanks to store the gases on-site. We consider a multi-period inventory routing problem with multiple products assuming deterministic demand rates and the proposed model is formulated as a linear mixed-integer program. We propose an incremental approach based on decomposing the set of customers in the original problem into sub-problems. The smallest sub-problem consists of the customer that needs to be delivered most urgently along with a set of its neighbors. We solve each sub-problem with the number of customers growing successively by providing the solution of the previously solved sub-problem as an input. Each sub-problem is then solved with a randomized local-search heuristic method. We also propose an objective function that drives the local-search heuristics toward a long-term optimal solution. The main purpose of this paper is to develop a solution methodology appropriate for large-scale real-life problem instances particularly in industrial gas distribution.